Neonatal Nurses' Beliefs, Knowledge, and Practices in Relation to Sudden Infant Death Syndrome Risk-Reduction Recommendations. (June 2015) - Barsman, Sarah Gutin; Dowling, Donna A.; Damato, Elizabeth G.; Czeck, Pamela; Dowling, Donna
<x xml:space="preserve">Abstract</x> Background: Sudden infant death syndrome (SIDS) remains the third leading cause of infant death in the United States and the leading cause of death beyond 1 month of age. In 2011, the American Academy of Pediatrics (AAP) released the newest SIDS risk-reduction recommendations, which address healthcare providers in neonatal intensive care units (NICUs). Little is known about neonatal nurses' SIDS prevention strategies since the release of these newest recommendations. Purpose: To assess neonatal nurses' beliefs, knowledge, and practices regarding SIDS prevention in both the NICU and step-down transitional care unit (TCU). Methods: A prospective-descriptive design was used. The 33-item SIDS Risk-Reduction Questionnaire was distributed to a convenience sample of nurses in a level III NICU/TCU in the Midwest. Results: Two hundred questionnaires were distributed; 96 (48%) were returned completed. Fifty-three percent of nurses strongly agreed that SIDS recommendations make a difference in preventing SIDS and 20% strongly believed that parents model SIDS prevention practices employed by staff. A majority of nurses correctly identified 2011 recommendations. Sixty-three percent of nurses often or always gave parents verbal information and 28% often or always gave parents written information regarding SIDS. Differences were seen between NICU and TCU nurses concerning beliefs and practices, suggesting that TCU nurses more consistently follow SIDS recommendations. Implications for Practice: Increased neonatal nursing and parental education regarding SIDS prevention and updated hospital policies promoting safe sleep are paramount. Implications for Research: Larger multicenter studies in level II/III NICUs are needed to provide further data on SIDS attitudes and practices.